2021
DOI: 10.1073/pnas.2107306118
|View full text |Cite
|
Sign up to set email alerts
|

Upslope migration of snow avalanches in a warming climate

Abstract: Snow is highly sensitive to atmospheric warming. However, because of the lack of sufficiently long snow avalanche time series and statistical techniques capable of accounting for the numerous biases inherent to sparse and incomplete avalanche records, the evolution of process activity in a warming climate remains little known. Filling this gap requires innovative approaches that put avalanche activity into a long-term context. Here, we combine extensive historical records and Bayesian techniques to construct a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 43 publications
4
21
0
1
Order By: Relevance
“…When the regional temperature increases by 1 °C, the active time for wet snow avalanches advances by approximately 8 days. Increasing winter air temperatures drove the advance and prevalence of wet avalanche activity in the Tianshan Mountains, given its continental snow climate, similar to previous findings reported in snow climate regions worldwide (Ballesteros-Cánovas et al 2018;Giacona et al 2021;Strapazzon et al 2021). Therefore, it is urgent to adjust the risk prevention and control time for wet snow avalanches and rationally arrange wet snow avalanche relief resources to improve the regional risk management of wet snow avalanche disasters.…”
Section: Impact Of Climate Warming On the Temporal Distribution Of Re...supporting
confidence: 73%
See 2 more Smart Citations
“…When the regional temperature increases by 1 °C, the active time for wet snow avalanches advances by approximately 8 days. Increasing winter air temperatures drove the advance and prevalence of wet avalanche activity in the Tianshan Mountains, given its continental snow climate, similar to previous findings reported in snow climate regions worldwide (Ballesteros-Cánovas et al 2018;Giacona et al 2021;Strapazzon et al 2021). Therefore, it is urgent to adjust the risk prevention and control time for wet snow avalanches and rationally arrange wet snow avalanche relief resources to improve the regional risk management of wet snow avalanche disasters.…”
Section: Impact Of Climate Warming On the Temporal Distribution Of Re...supporting
confidence: 73%
“…Existing studies have also reported that the behavior of snow avalanches has changed. There are significant regional differences in marine and transitional snow climates (Ballesteros-Cánovas et al 2018;Gratton et al 2020;Giacona et al 2021). The temperature increase rate in the Tianshan Mountains with a typical continental snow climate was 0.34 °C/10 years from 1960 to 2017, significantly higher than the global average temperature increase rate (Li et al 2020).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The number and area of glacier lakes has increased in most mountain regions of the globe (Shugar et al, 2020), and changes in the decadal occurrences of GLOFs has oscillated (Harrison et al, 2018), but it remains uncertain whether the frequency of GLOFs has increased over the longer term as is widely supposed (Harrison et al, 2018;Veh et al, 2022;Veh et al, 2019). Snow avalanches involving wet snow have increased in several regions and mostly at higher elevations (Ballesteros-Cánovas et al, 2018;Stoffel and Corona, 2018), whereas snow avalanches have become much less frequent at lower altitudes (Castebrunet et al, 2014;Giacona et al, 2021). As a consequence of increases in temperature and snowfall limits, rain-on-snow floods have increased in winter, but have started to decrease in spring (Freudiger et al, 2014).…”
Section: Process Chains and Climate Change In Mountain Regionsmentioning
confidence: 99%
“…In mountainous environments, mass movements are particularly sensitive to global warming (Gariano and Guzzetti, 2016; Stoffel and Corona, 2014). As air temperatures continue to rise, mass movements are expected to change in terms of their frequency or magnitude as well as in area affected (Hock et al, 2019; Giacona et al, 2021). Among these mass movements, rockfall is a major driver of landscape evolution on steep mountain flanks (Korup, 2006) and thus also presents a serious hazard in mountain regions across the globe (Bovis et al, 1985; Evans and Degraff, 2002).…”
Section: Introductionmentioning
confidence: 99%